2017
DOI: 10.1093/gji/ggx426
|View full text |Cite
|
Sign up to set email alerts
|

Site characterization at Groningen gas field area through joint surface-borehole H/V analysis

Abstract: A new interpretation of the horizontal to vertical (H/V) spectral ratio in terms of the Diffuse Field Assumption (DFA) has fuelled a resurgence of interest in that approach. The DFA links H/V measurements to Green's function retrieval through autocorrelation of the ambient seismic field. This naturally allows for estimation of layered velocity structure. In this contribution, we further explore the potential of H/V analysis. Our study is facilitated by a distributed array of surface and co-located borehole sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…4a) demonstrate the good convergence of the H/V after stacking (e.g. Spica et al 2017b). The quality of H/V retrieval in this frequency band is further verified by the spatial continuity of the spectral H/V amplitude along the line A-A' (Fig.…”
Section: H/v Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…4a) demonstrate the good convergence of the H/V after stacking (e.g. Spica et al 2017b). The quality of H/V retrieval in this frequency band is further verified by the spatial continuity of the spectral H/V amplitude along the line A-A' (Fig.…”
Section: H/v Analysismentioning
confidence: 92%
“…Piña-Flores et al 2016). Independent information, such as surface wave dispersion (Scherbaum et al 2003;Piña-Flores et al 2016;Lontsi et al 2016) or H/V measurements recorded at different depths (Lontsi et al 2015;Spica et al 2017b) or locations (Perton et al 2017) all provide opportunities to reduce this non-uniqueness. Additionally, Perton et al (2017) suggested that the H and V components could be considered independently to assess the reliability of H/V and to characterize properties of the noise field illumination.…”
Section: Introductionmentioning
confidence: 99%
“…Using borehole interferometry, Hofman et al (2017), Spica, Perton, Nakata, et al (2017), and Noorlandt et al (2018) retrieved P and S waves inside the G-array's boreholes and Zhou and Paulssen (2017) characterized P-and S-wave velocities of the reservoir using borehole interferometry using the SDM and ZRP arrays. Table 1 presents a summary of our observations related to the retrieved wavefield based on ASF correlations in the near ▴ Figure 6.…”
Section: Using the Loppersum Arraymentioning
confidence: 99%
“…Fundamental-mode surface waves (Rayleigh and Love waves) are now routinely extracted from ASF to image the crust, the lithosphere, and the upper mantle (e.g., Bensen et al, 2008) at global (Nishida et al, 2009), regional (Shapiro et al, 2005), and local scales (e.g., Spica, Perton, and Legrand, 2017). Body-wave retrieval is more challenging; however, recent exam-ples attest to that possibility (e.g., Roux et al, 2005;Ruigrok et al, 2011;Poli et al, 2012;Nakata et al, 2015;Spica, Perton, Nakata, et al, 2017). In active producing fields (oil, gas, or geothermal), ASF interferometry of geophones in boreholes is emerging as a method well suited for permanent reservoir monitoring (e.g., Hillers et al, 2015;Behm, 2017) or to assess the P-and S-velocity structure of such reservoirs (e.g., Miya-zawa et al, 2008;Zhou and Paulssen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Records from all four geophones of the stations and their surface accelerograph (discussed in Sect. 2.3) have been used in work related to the site properties of the locations of the G-stations, such as the study of Spica et al (2017).…”
Section: Borehole Instrumentsmentioning
confidence: 99%